Capturing patient anatomy for designing and manufacturing personalized prostheses. (February 2022) - Paxton, Naomi C; Nightingale, Renee C; Woodruff, Maria A
Graphical abstract: Highlights: Prostheses can be personalized using advanced 3D scanning technologies. 3D surface scanning is an emerging trend for capturing patient anatomy. Automated workflows for translating patient scan data are becoming more accessible. Abstract : Prostheses play a critical role in healthcare provision for many patients and encompass aesthetic facial prostheses, prosthetic limbs and prosthetic joints, bones, and other implantable medical devices in musculoskeletal surgery. An increasingly important component in cutting-edge healthcare treatments is the ability to accurately capture patient anatomy in order to guide the manufacture of personalized prostheses. This article examines methods for capturing patient anatomy and discusses the degrees of personalization in medical manufacturing alongside a summary of current trends in scanning technology with a focus on identifying workflows for incorporating personalization into patient-specific products. Over the next decade, with increased harmonization of both personalization and automated prosthetic manufacturing will be the realization of improved patient compliance, satisfaction, and clinical outcomes.